The Effect of Technical Quality, Functional Quality, and Hospital Image on Patient Satisfaction Mediated by Patient Experience: A Study of Periodontics Specialist Services at RSGMP Unsoed - Dewi Ayu Pratiwi; Suliyanto Suliyanto (CV. Green Publisher Indonesia, 2026)
This study aims to analyse the effect of technical quality, functional quality, and hospital image on patient satisfaction, with patient experience as a mediating variable, in periodontics specialist services at RSGMP Unsoed. The study employs a quantitative approach using a survey method. The research population comprises all patients who have received periodontics specialist services, with a purposive sampling technique yielding a total of 120 respondents. Data collection was conducted using a structured questionnaire based on indicators of technical quality, functional quality, hospital image, patient experience, and patient satisfaction. Data were analysed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) method with the aid of SmartPLS software to test both the measurement model and the structural model. The results indicate that technical quality, functional quality, and hospital image each have a positive and significant effect on patient experience. Furthermore, patient experience has a positive and significant effect on patient satisfaction. The mediation test results demonstrate that patient experience significantly mediates the effect of technical quality, functional quality, and hospital image on patient satisfaction. These findings confirm that patient satisfaction is not solely determined by clinical outcomes, but also by the patient experience throughout the service process. Therefore, hospitals need to enhance the technical and functional quality of their services and maintain a consistent hospital image in order to cultivate a positive patient experience and continuously improve patient satisfaction.